2015
DOI: 10.1038/srep09820
|View full text |Cite|
|
Sign up to set email alerts
|

Non-equilibrium scale invariance and shortcuts to adiabaticity in a one-dimensional Bose gas

Abstract: We present experimental evidence for scale invariant behaviour of the excitation spectrum in phase-fluctuating quasi-1d Bose gases after a rapid change of the external trapping potential. Probing density correlations in free expansion, we find that the temperature of an initial thermal state scales with the spatial extension of the cloud as predicted by a model based on adiabatic rescaling of initial eigenmodes with conserved quasiparticle occupation numbers. Based on this result, we demonstrate that shortcuts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 50 publications
2
68
0
Order By: Relevance
“…However, the linear increase in system energy is ubiquitously observed, also in experiments in the spatial continuum [34]. This effect is captured by the continuum heating term in Eq.…”
Section: A Master Equation In the Luttinger Descriptionmentioning
confidence: 85%
“…However, the linear increase in system energy is ubiquitously observed, also in experiments in the spatial continuum [34]. This effect is captured by the continuum heating term in Eq.…”
Section: A Master Equation In the Luttinger Descriptionmentioning
confidence: 85%
“…Concerning the relevance of the interacting Luttinger model, before closing the section, we would like to mention that only recently pioneering experiments in ultra-cold gases both in and out of equilibrium explored the transient and prethermalization dynamics of systems [16][17][18][19][20][21][22][23][24][25][26][68][69][70] effectively described by a quadratic Luttinger model, the bosonic theory of the Hamiltonian in Eq. (2.2).…”
Section: Interacting Luttinger Liquidmentioning
confidence: 99%
“…In particular, in Refs. [16][17][18]24] prethermal states in the relative phase of a suddenly split condensate have been identified that have been stable on the experimentally accessible time scales. For the latter experiments, the cubic nonlinearity studied in the present work constitutes the leading order correction to the quadratic theory in a gradient expansion.…”
Section: Interacting Luttinger Liquidmentioning
confidence: 99%
“…[40,41]); (iii) Application of imperfect external drivings which do not allow for an exact adiabatic transfer, but close enough for most practical purposes (e.g. [42][43][44]). …”
Section: Introductionmentioning
confidence: 99%